Proceedings of the Proceedings of the 1st Hasanuddin International Conference on Social and Political Sciences, HICOSPOS 2019, 2020
DOI: 10.4108/eai.21-10-2019.2291531
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Youth Radicalism and Socio-Religious Intolerance in Social Media

Abstract: This study is part of a two-years research on youth radicalisme and socioreligious intolerance in social media. It is aimed to map the aspects of radicalism and intolerance; and to assess the degree of radicalism and intolerance in the use of social media by young generation. The current result shows that there is strong correlation between youth attitudes in real and virtual worlds. In general young generation is relatively tolerant towards various social groups in both real life and cyberspace, with an excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The reaction of European youth to Islamic radicalism and Islamophobia is studied by Jason (2015) (Germany Pegida protests: Rallies over Islamisation) and by Kadri (2015) (Paris attacks prompt fresh concerns about online Islamophobia) (Finlay & Hopkins, 2020). Youth's radicalism and socio-religious intolerance found on social networks were investigated by Indonesian researchers (Burhanuddin et al, 2019). Thus, the analysis of publications showed that our study is one of the few ones considered in the context of youth's disposition of radicalism sentiments.…”
Section: Discussionmentioning
confidence: 96%
“…The reaction of European youth to Islamic radicalism and Islamophobia is studied by Jason (2015) (Germany Pegida protests: Rallies over Islamisation) and by Kadri (2015) (Paris attacks prompt fresh concerns about online Islamophobia) (Finlay & Hopkins, 2020). Youth's radicalism and socio-religious intolerance found on social networks were investigated by Indonesian researchers (Burhanuddin et al, 2019). Thus, the analysis of publications showed that our study is one of the few ones considered in the context of youth's disposition of radicalism sentiments.…”
Section: Discussionmentioning
confidence: 96%